PENGEMBANGAN MATERI KETERAMPILAN SOSIAL BAGI SISWA KELAS XI SMA - Yurnelis '; Tri Umari; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The existence of the behavior of children who encountered such as aloof, nervous of speaking in front of and unable to adapt to the environment, this material is prepared using methods of research and development (R and D). This study aims at drafting material about social skills necessary for high school students in terms of the clarity of the material, the material systematics, image support, video support completeness of the materials and to know the quality of this materials. Materials validated by the supervisor I and 2 BK FKIP UR, Professor by the teacher guidance and counseling , and 40 students . material consists of Characteristics Understanding Social skills Social skills, factors affecting Social skills, Social skills examples and the importance of skills development materials social. Result research shows that be produced quality materials that are in the category '' good '', with the acquisition of a score of 4.15 for the entire aspect of the assessment.Key words: Guidance and Counseling, Social Skills, Senior high school